Role of adiponectin in osteoarthritis - Feng, Xinyuan; Xiao, Jiaying; Bai, Lunhao (Frontiers in Cell and Developmental Biology, 2022)
Abstract Background Osteoarthritis (OA) is a widespread and most common joint disease; the progression of OA includes cartilage degradation. The molecular mechanisms of action in chondrocytes may provide insights into treatment methods for OA. Adiponectin is an adipokine with many biological functions in the development of OA. Results Numerous studies have illustrated that adiponectin has diverse biological effects, such as inhibition of cell apoptosis. It regulates various functions in different organs, including muscle, adipose tissue, brain, and bone, and regulates skeletal homeostasis. Therefore, it is reasonable to infer that adiponectin affects the development of OA. Conclusion In this review, we summarize the molecular pathways and mechanisms of action of adiponectin in chondrocyte inflammation and death and the pathogenesis of OA. We also review the research on adiponectin as a target for treating OA. These studies provide a novel perspective to explore more effective treatment options considering the complex interrelationship between inflammation and metabolism in OA. Keywords: adiponectin, autophagy, Osteoarthritis, apoptosis, pyroptosis